A case of non‐ischemic priapism in a healthy 7‐year‐old boy - Danielle Mercurio; James O'Donnell (Journal of the American College of Emergency Physicians Open)
Abstract Priapism is a urologic emergency more commonly encountered in the adult population. Causes include medication adverse effect, chronic disease, malignancy, dialysis, spinal cord lesions, trauma, infection/inflammation, neuropathy, and idiopathic. Evaluation and treatment focus on identifying and eliminating etiology along with supportive measures. If medical management is not effective, surgery is usually performed to preserve function.